2020
DOI: 10.1039/d0nr00271b
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical reaction to control the near-infrared photoluminescence properties of single-walled carbon nanotubes

Abstract: A simple one-step operation to control the PL properties of SWNTs by ultrasonic irradiation was developed with an appropriate surfactant under the optimized conditions of the irradiation time, SWNT concentration, and reaction atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The different behavior of these peaks can be explained by the lack of a significant absorption band in the red-shifted PL region. However, as it has been reported that upconversion PL is observed for functionalized SWNTs upon excitation of the quantum defects, the effects of reabsorption at the E 11 ** wavelength cannot be neglected completely. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different behavior of these peaks can be explained by the lack of a significant absorption band in the red-shifted PL region. However, as it has been reported that upconversion PL is observed for functionalized SWNTs upon excitation of the quantum defects, the effects of reabsorption at the E 11 ** wavelength cannot be neglected completely. ,, …”
Section: Resultsmentioning
confidence: 99%
“…However, as it has been reported that upconversion PL is observed for functionalized SWNTs upon excitation of the quantum defects, the effects of reabsorption at the E 11 ** wavelength cannot be neglected completely. 22,24,36 It has been reported that the quantum defects of SWNTs are advantageous because they can be excited using the E 11 absorption band, which is stronger than the E 22 absorption band (see Figure S1). At low concentrations, E 11 excitation was more efficient than E 22 excitation for E 11 ** PL in H-SWNTs-xylyl (0.0315).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We hypothesize that the slight increase in the I D /I G ratios may be caused by chlorine and bromine radicals addition to the SWCNTs, as these reactive species may be generated by sonolysis of the halogenated solvents 34 , 35 . Maeda et al showed that the sonication of SWCNTs in water might give oxygen-containing reactive species, which can functionalize the surface 36 . Analogously, it should be possible to form reactive halogen intermediates from the investigated halogen solvents.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46][47] Nevertheless, designing hydrophobic dendrons as the binding sites provides a high degree of control over their direct interaction with the SWCNT surface. 48 In this study, we present polymer-dendron hybrids as modular amphiphilic agents for the suspension of SWCNTs in aqueous media. The polymer-dendron hybrids designed for this study are amphiphilic macromolecules consisting of three building blocks (Fig.…”
Section: Introductionmentioning
confidence: 99%